Investigation of battery energy storage system for providing ancillary services in electricity market - Ong, Zi Zhao (2018)
Renewable energy sources and electrified vehicles are increasingly adopted in many countries to reduce greenhouse gas emissions. This will require additional investment in electricity infrastructure to tackle problems that arise from this paradigm shift. Battery energy storage can help mitigate some of the problems such as the intermittency of renewable energy sources and provide ancillary services to the grid. The cost of battery storage has been decreasing over the years with the advancement in technology, thus it will become more economical for investment by power systems operators, generators or end users of electricity. Various battery storage technologies will be discussed and one will be chosen to be investigated for its economic viability in Singapore electricity market. The operation cost model and technical constraints of the battery will be formulated. The model will be processed by an optimization software. Numerical analysis will be conducted to derive the maximum possible profit. The economic viability of investing in a battery storage solution will be determined by the outcome of the numerical analysis.